A comprehensive approach to concrete strength testing: combining destructive, non-destructive and wireless sensor methods - Taubaldy, I.; Daniyar , Akhmetov; Rakisheva , A. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
To assess the condition of the structures of buildings and structures it is necessary to perform a comprehensive analysis of the factors affecting their performance characteristics - concrete strength, thermal conductivity and humidity of concrete, frost resistance, and water resistance. However, with a variety of controllable parameters the control of concrete strength takes a special place because the main factor of structure condition estimation is the correspondence of actual concrete strength to the design requirements. The paper presented the basic methods of concrete strength control which are used while examining the constructions of buildings and structures. The results of the experiments comparing the data obtained by destructive, non-destructive, and alternative methods were investigated. A wireless sensor of concrete strength, produced in Kazakhstan, was used when carrying out the tests with the use of smart technology. And the graphical quantitative-qualitative method "web" used by the authors allowed to determine and identify the features of each method.